Ethical and Legal Aspects of Research Involving Animal Subjects in Indonesia - Sugihardana, Danang; Awandi Putri, Sabrina Diyang (Alauddin Law Development Journal (ALDEV), 2024)
Advances in science often benefit human health but can also involve sacrifices, particularly when animals are used as research subjects. This study explores the ethical and legal aspects of using animals in research, focusing on improving understanding and compliance with animal welfare regulations in Indonesia. The research aims to analyze laws and ethical principles such as the 3R and 5F to ensure humane treatment of animals. Utilizing a normative legal approach and library research methodology, this study evaluates various regulations, including laws, government policies, and institutional guidelines concerning animal welfare in research. The novelty of this research lies in its comprehensive analysis of how legal requirements intersect with ethical considerations, underscoring the need for ethics committees to oversee research practices. The findings emphasize that while animal research is essential for scientific progress, strict adherence to regulations is necessary to protect animals from abuse and ensure ethical research practices.